INTEGRASI LANDASAN PSIKOLOGIS DAN SOSIOLOGIS DALAM MANAJEMEN PENDIDIKAN: SYSTEMATIC LITERATURE REVIEW - Windi Widayanti; Euis Fidyana; Iis Setianingsih; Anton Setiabudi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing complexity of educational management in the era of social change and digital transformation requires a holistic approach that goes beyond administrative and technical considerations. Integrating psychological and sociological foundations has become essential to understand individual behavior and social dynamics within educational institutions. This study aims to examine the integration of psychological and sociological foundations in educational management through a Systematic Literature Review (SLR). The review analyzed national and international scholarly articles published between 2010 and 2025 and retrieved from databases such as Google Scholar, ERIC, Scopus, and Indonesian journal portals. The findings indicate that the integration of psychological and sociological perspectives contributes significantly to effective leadership, human resource management, organizational culture, and community engagement in education. Such integration supports the development of a more adaptive, human-centered, and context-sensitive educational management framework. This study provides a conceptual contribution to educational management theory and offers practical insights for educational leaders and policymakers in designing sustainable and inclusive management practices. Keywords: educational management, psychological foundations, sociological foundations, systematic literature review, organizational effectiveness